Pengaruh Alih Fungsi Tanah Ulayat Menjadi Kawasan Wisata terhadap Lingkungan di Kenagarian Tarantang - Febrian Maulana; Muhammad Syukri Azhari; Pamelda Ariska; Dewi Puspasari; Ariffa Mutri Muslimah; Livhia Putri Hardiyanti; Eirene Yosephine Rintonga; Yoskar Kadarisman; Dian Kurnia Anggreta; Mardhatillah Mardhatillah (International Forum of Researchers and Lecturers, 2025)
Communal land in Kenagarian Tarantang has undergone conversion into tourism areas, bringing impacts on local environmental conditions. This study aims to explain the forms of communal land conversion into tourist areas, environmental conditions after conversion, and its impact on the environment in Kenagarian Tarantang. The research employed a quantitative associative approach involving 50 respondents randomly selected from 789 households. Data were collected through questionnaires, field observations, and interviews, then analyzed using simple regression analysis. The results showed that communal land conversion occurred intensively for homestay construction and tourism facilities with a total score of 1121 in the good category. Environmental conditions were generally well-controlled with a score of 983 in the very good category, although there were impacts such as reduced vegetation and decreased water quality. Regression analysis confirmed a significant influence between communal land conversion and environmental conditions at 18.49 percent with a significance value of 0.002. Community participation in maintaining the cleanliness of tourism areas was very good, however, stricter government supervision, reforestation programs, and adequate waste management are needed to prevent ecosystem degradation in the future.